Performance of hedges and their characteristics for buffering noise in urban residential areas - Mohamed, Noorizan; Ina Krisantia, (Faculty of Design & Architecture, Universiti Putra Malaysia, 2009)
Many environmental designers are currently searching for better solution on reducing noise frequency levels in housing estates. Planting hedges as buffer is commonly done but the question is whether they serve the right function and purpose. In order to determine the plant performance, a sound level meter was used to detect noise reduction from commonly planted hedges in residential areas of Putrajaya and Kuala Lumpur. The source of sound for measurement was from a grass trimmer that is commonly heard in residential areas. This paper highlights the performance of selected local plants in absorbing the noise frequency. A statistical analysis showed that hedges such as Baphia nitida and Bixa orellana of sufficient heights and length are promising and have a good potential in controlling sound levels. Ixora "sunkist" with small leaves and with more layers of planting also provides similar result. Until a controlled experimental study is carried out, this initial finding would be useful in plant selection for buffering noise in local landscape projects